THU0102 Apo(a), a potential link between atherosclerosis and arthritis. (1st June 2001) - Busso, N; Dudler, J; Salvi, R; Péclat, V; Darioli, R; Nicod, P; So, A; Mooser, V
Abstract : Background: Patients with rheumatic diseases have an excess in cardiovascular morbidity and mortality, suggesting the presence of common pathogenic abnormalities for both atherosclerosis and arthritis. One particularly atherogenic apolipoprotein, apo (a), an homologue of plasminogen, may be involved by competing with plasminogen for fibrin binding and by interfering with fibrinolysis. Objectives: To study the expression of apo (a) in arthritic joints. Methods: Human studies: synovial fluid and plasma from patients with osteoarthritis (OA, n = 8), rheumatoid arthritis (RA, n = 12) and other types of inflammatory arthritis (n = 12) and synovial tissues from OA and RA patients were collected. Apo (a) was quantitated by ELISA and in tissues also by RNase protection. Moreover, immunohistochemical analyses of apo (a) and fibrin were performed on synovial tissues. Animal studies: antigen-induced arthritis (AIA) was induced in genetically modified mice (LDL-receptor deficient (LDL-R -/-) mice expressing a human apoB-100 transgene (hApoB +/+) and a human apo (a) transgene (apo (a) ±)). Joint inflammation was assessed by technetium scintigraphy and histology. Results: We detected the presence of apo (a) as a full-length glycoprotein in human arthritic joints. The amount of apo (a) in synovial fluid rose in proportion to plasma apo (a) levels and was higher in inflammatory arthritides than in osteoarthritis. In addition, apo (a) immunoreactive material, but not apo (a) transcripts, was detected in arthritic synovial tissues. This data indicated that synovial fluid apo (a) originates from the circulation and that diffusion through synovial tissue is facilitated in inflammatory types of arthritis. In synovial tissues, apo (a) colocalized with fibrin. These observations could be reproduced in a model of antigen-induced arthritis, using transgenic mice expressing human apo (a). In this particular mouse model, the presence of apo (a) did not change joint inflammation. Conclusion: Even if the presence of apo (a) did not change the severity of AIA, we speculate that when levels of apo (a) are sufficiently high to inhibit fibrinolysis in the joints, apo (a) may exacerbate in humans the severity of the disease.